1983
DOI: 10.1037/0278-7393.9.2.263
|View full text |Cite
|
Sign up to set email alerts
|

Schematic information, attention, and memory for places.

Abstract: Recall and recognition of various aspects of three places were studied under incidental and intentional conditions. Data showed that subjects passing through a place incidentally remembered structural features such as walls better than variable features such as furniture. On the other hand, subjects passing through a place knowing they will be tested for memory of its remembered the variable elements better than the structural elements. The results are interpreted in terms of intentionally governed coding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0
1

Year Published

1985
1985
1998
1998

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 6 publications
1
6
0
1
Order By: Relevance
“…In a related study Salmaso, Baroni, Job, and Peron (1983) reported that the encoding instructions given to subjects significantly varied their memory for types of objects in a scene. Subjects were walked through an office area and then tested on their memory for the physical appearance of room frame objects (e.g., floor, walls, ceiling light) and schema consistent objects (e.g., chair, waste basket, card index).…”
Section: Methodsmentioning
confidence: 99%
“…In a related study Salmaso, Baroni, Job, and Peron (1983) reported that the encoding instructions given to subjects significantly varied their memory for types of objects in a scene. Subjects were walked through an office area and then tested on their memory for the physical appearance of room frame objects (e.g., floor, walls, ceiling light) and schema consistent objects (e.g., chair, waste basket, card index).…”
Section: Methodsmentioning
confidence: 99%
“…Hess & Satterfield Tate, 1991). Following the procedures in the studies of Brewer and Treyens (1981), Pezdek et al (1989), andSalmaso, Baroni, Job, andMainardi Peron (1983), we directed participants to an office room containing expected and unexpected objects. After having viewed the objects, subjects were given recognition tests on item and token information.…”
mentioning
confidence: 99%
“…La percepción espacial es un proceso constructivo que implica entre otras cosas la extracción de características (procesos de abajo-arriba), pero también la confirmación de expectativas y la interpretación en base al conocimiento ptevio, esquemas y metas (procesos de arriba-abajo). Salmaso et al (1983) y Brewer y Treyens (1981) encontraron que se recuerda mejor la información sobre lugares congruente con un esquema previo sobre los mismos, que aquella no relevante o inesperada según el esquema. El efecto de la congruencia, sin embargo, está modulado por la saliencia de la información así como por la adopción de estrategias intencionales o incidentales y no favorece el reconocimiento.…”
Section: Conocimiento Espacialunclassified